Animal versus plant protein and adult bone health: A systematic review and meta-analysis from the National Osteoporosis Foundation. - Marissa M Shams-White; Mei Chung; Zhuxuan Fu; Karl L Insogna; Micaela C Karlsen; Meryl S LeBoff; Sue A Shapses; Joachim Sackey; Jian Shi; Taylor C Wallace; Connie M Weaver (PLoS ONE)
Background Protein may have both beneficial and detrimental effects on bone health depending on a variety of factors, including protein source. Objective The aim was to conduct a systematic review and meta-analysis evaluating the effects of animal versus plant protein intake on bone mineral density (BMD), bone mineral content (BMC) and select bone biomarkers in healthy adults. Methods Searches across five databases were conducted through 10/31/16 for randomized controlled trials (RCTs) and prospective cohort studies in healthy adults that examined the effects of animal versus plant protein intake on 1) total body (TB), total hip (TH), lumbar spine (LS) or femoral neck (FN) BMD or TB BMC for at least one year, or 2) select bone formation and resorption biomarkers for at least six months. Strength of evidence (SOE) was assessed and random effect meta-analyses were performed. Results Seven RCTs examining animal vs. isoflavone-rich soy (Soy+) protein intake in 633 healthy peri-menopausal (n = 1) and post-menopausal (n = 6) women were included. Overall risk of bias was medium. Limited SOE suggests no significant difference between Soy+ vs. animal protein on LS, TH, FN and TB BMD, TB BMC, and bone turnover markers BSAP and NTX. Meta-analysis results showed on average, the differences between Soy+ and animal protein groups were close to zero and not significant for BMD outcomes (LS: n = 4, pooled net % change: 0.24%, 95% CI: -0.80%, 1.28%; TB: n = 3, -0.24%, 95% CI: -0.81%, 0.33%; FN: n = 3, 0.13%, 95% CI: -0.94%, 1.21%). All meta-analyses had no statistical heterogeneity. Conclusions These results do not support soy protein consumption as more advantageous than animal protein, or vice versa. Future studies are needed examining the effects of different protein sources in different populations on BMD, BMC, and fracture.